Dose recommendations for intravenous colistin in pediatric patients from a prospective, multicenter, population pharmacokinetic study - Noppadol Wacharachaisurapol; Warumphon Sukkummee; Orawan Anunsittichai; Panida Srisan; Siriporn Sangkhamal; Prawat Chantharit; Warunee Punpanich Vandepitte; Thitima Wattanavijitkul; Thanyawee Puthanakit (International Journal of Infectious Diseases, 2021)
Objectives: The aim of this study was to describe the population pharmacokinetics of intravenous colistin use in children and to propose optimal dosage regimens. Methods: A prospective, multicenter, population pharmacokinetic (PPK) study was conducted. Phoenix 64 version 8.3 was used for the PPK analysis. Simulations were performed to estimate the probability of target attainment for patients achieving target plasma colistin average steady-state concentrations (Css,avg). Results: A total of 334 plasma colistin concentrations were obtained from 79 pediatric patients with a median age (interquartile range) of 2.6 years (0.8−6.8 years); 73 (92.4%) were admitted to intensive care units. Colistin pharmacokinetics were adequately described by a one-compartment model with first-order elimination along with serum creatinine (SCr) as a significant covariate in colistin clearance. The simulation demonstrated that the recommended dose of 5 mg of colistin base activity (CBA)/kg/day resulted in 18.2−63.0% probability of achieving a target Css,avg of 2 mg/l. With a lower targeted Css,avg of 1 mg/l, colistin dosing with 7.5 mg and 5 mg of CBA/kg/day were adequate for children with SCr levels of 0.1−0.3 mg/dl and >0.3 mg/dl, respectively. Conclusions: SCr is a significant covariate in colistin clearance in children. Colistin dosing should be selected according to the patient's SCr level and the desired target Css,avg.